Strategy Selection to Enhance Customer Data Quality using AHP: Case Study of General Insurance Company (PT XYZ) - Adinda Rizkita Syafira; Achmad Nizar Hidayanto; Widijanto Satyo Nugroho; Rahmat Mustafa Samik-Ibrahim (IJCCS (Indonesian Journal of Computing and Cybernetics Systems))
This study examines strategies to enhance customer data quality at PT XYZ, a general insurance company, which is crucial for strategic decision-making and revenue growth. The importance of this topic lies in its potential to significantly improve operational efficiency and customer satisfaction. The Analytical Hierarchy Process (AHP) is utilized to select the optimal strategy from available alternatives. The research begins by establishing criteria and identifying alternative strategies to improve customer data quality. Expert evaluations are conducted based on four criteria: cost, time, security, and availability. Four experts are involved, chosen for their expertise in technology and organizational impact. The experts include a Senior IT Business Intelligence, a Data Analyst, a Unit Head of IT Infrastructure & Security Department, and a Division Head of Digital. The findings highlight that the strategy of Strengthening Collaboration Across Departments, with a value of 0.455, is the most effective. This strategy emphasizes interdepartmental cooperation to enhance data quality. The results underscore the long-term benefits of improved operational efficiency and customer satisfaction despite initial investment challenges, demonstrating the practical application of AHP in organizational settings.